2014
DOI: 10.1007/s10490-014-9385-9
|View full text |Cite
|
Sign up to set email alerts
|

How do business groups’ small world networks effect diversification, innovation, and internationalization?

Abstract: Small world networks which demonstrate better group cohesiveness have attracted much theoretical attention in enhancing performance and creativity in strategic management. Yet, empirical studies of the benefits that can accrue to business groups' strategic or economic outcomes remain scarce in the business group literature. Conceptualizing the business group as an embedded group network, we investigate the previously untested role of a small world group structure on relationships with group (industrial) divers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 89 publications
(86 reference statements)
4
36
0
2
Order By: Relevance
“…First, we find a positive relationship between BG affiliation and foreign subsidiary performance which shows that BG affiliation benefits can be transferred across international boundaries to second‐level affiliates, that is, to foreign subsidiaries of BG members. This finding complements those of previous studies which have found differences in the internationalization process and performance between BG affiliated and unaffiliated MNEs (Chen & Jaw, ; Elango & Pattnaik, ; Garg & Delios, ; Kim et al, ). To the best of our knowledge, ours is the first study of its kind to establish a direct connection between BG affiliation and foreign subsidiary financial performance.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…First, we find a positive relationship between BG affiliation and foreign subsidiary performance which shows that BG affiliation benefits can be transferred across international boundaries to second‐level affiliates, that is, to foreign subsidiaries of BG members. This finding complements those of previous studies which have found differences in the internationalization process and performance between BG affiliated and unaffiliated MNEs (Chen & Jaw, ; Elango & Pattnaik, ; Garg & Delios, ; Kim et al, ). To the best of our knowledge, ours is the first study of its kind to establish a direct connection between BG affiliation and foreign subsidiary financial performance.…”
Section: Discussionsupporting
confidence: 90%
“…These kinds of market-based advantages can augment the competitiveness of affiliated firms vis-àvis their unaffiliated rivals-and allow them to capture monopolistic or Ricardian rents (Cuervo-Cazurra & Genç, 2011;Peteraf, 1993). The second source of strength stems from political and social connections nurtured over time (Bucheli, Salvaj, & Kim, 2019;Chen & Jaw, 2014;Guillén, 2000;Hu, Cui, & Aulakh, 2019;Mukherjee, Makarius, & Stevens, 2018). BGs may leverage such connections to influence government policy to the benefit of their affiliates (Hu et al, 2019;Mukherjee et al, 2018).…”
Section: Bg Affiliation Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies focus on the impact of corporate ownership on the processes of diversification (Chung, 2013;Hernández-Trasobares & Galve-Górriz, 2016;Schmid et al, 2015;Sanchez-Bueno & Usero, 2014). Geographical diversification of business companies (Chonghui et al, 2013;Thoumrungroje & Tansuhaj, 2005;Gaur & Delios, 2015;Qian et al, 2013;Yahaya et al, 2009;Mauer et al, 2015), diversification risks (Busse et al, 2014;Yücel & Önal, 2015), the processes of diversification in business networks (Kim et al, 2014;Chen & Jaw, 2014) are areas of continuous interest among researchers.…”
Section: Preconditions and Conditions For Decisionmaking On Corporatementioning
confidence: 99%
“…This credit may be insufficient in formal circumstances of a dispersed and atomised large network (as in the case of ZB). Smaller group structures tend to better facilitate strategic and economic outcomes for their members (Chen & Jaw, 2014, p. 1019. In the case of P and other high-tech industry born global companies, rapid internationalisation necessitates the exploitation of temporary network nodes and specialised fora (Smith, Ryan, & Evers, 2015, p. 297).…”
Section: The Typology Of Relationship Capital Mediating Agentsmentioning
confidence: 99%